2002
DOI: 10.1006/brln.2001.2503
|View full text |Cite
|
Sign up to set email alerts
|

Graded Aspects of Morphological Processing: Task and Processing Time

Abstract: Effects on targets of orthographically (O) and semantically (S) related primes were compared with morphologically related (M) primes in the lexical decision, naming, and go/no go naming tasks. The overall pattern typified the graded nature of morphological processing. Morphological relatedness produced facilitation whose magnitude varied across a range of stimulus onset asynchronies (SOAs of 66-300 ms) and tasks. The effect of semantic and orthographic similarity also depended on SOA and on task. Importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…Previous research found that morphological priming effects tend to be smaller in the naming task relative to effects found in the lexical decision task (Drews & Zwitscrlood, 1995;Feldman & Prostko, 2002). However, this comparison was made with adult readers whose naming responses are very fast.…”
Section: Discussionmentioning
confidence: 83%
“…Previous research found that morphological priming effects tend to be smaller in the naming task relative to effects found in the lexical decision task (Drews & Zwitscrlood, 1995;Feldman & Prostko, 2002). However, this comparison was made with adult readers whose naming responses are very fast.…”
Section: Discussionmentioning
confidence: 83%
“…Earlier studies in English (Feldman & Prostko, 2002;Rastle et al, 2000), French (Seguí & Grainger, 1990), and German (Drews & Zwitserlood, 1995) have consistently shown that form-priming effects dissipate at prime exposure durations exceeding 300 ms. In contrast, Experiment 1 in the present research provides clear evidence of form priming in Hindi, despite the use of relatively long prime exposures (136 and 680 ms).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that the effect of orthographic and/or phonological overlap in priming is sensitive to the processing time of the prime. Effects of formal overlap tend to decrease as the processing time of the prime increases, whereas prime duration has an opposite effect on semantic similarity; semantic effects tend to increase with longer processing time (Feldman, 2000;Feldman & Prostko, 2002;Feldman & Soltano, 1999). Manipulation of processing time can reveal contributions of formal and semantic dimensions to morphological processing and how the magnitudes of these factors change over time and with particular task parameters.…”
Section: Suffixed Irregular Verbsmentioning
confidence: 99%